PENGENTASAN KETERPURUKAN ANAK-ANAK PESISIR AKIBAT JERAT KEKERASAN SOSIAL MELALUI SANASIR DI DESA BADDURIH PAMEKASAN - Mansur; Fahmi Assulthoni; Taufik; Moh Safik; Khoyyilah (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2024)
The purpose of this service research is to identify children who are victims of social violence, and to find practical and simultaneous solutions in solving social violence in children. the method used is Participatory Action Research (PAR), the PRA technique is accompanied by an expansion of the scale of the movement. The alleviation strategy uses the INSPIRE - WHO concept which has proven its application in several countries since 2016. As a result, 2 Mystical Gangs and BDR-Crew Gangs were found with a total of 47 school-age children. The formation of SANASIR (School for Coastal Children) is a non-physical vehicle for alleviating the adversity of coastal children from the snare of social violence that the community is fighting for in the format of recitation, column, kambrat, fatayat, Muslimatan, Hadrah Arts and Ul-Daul Traditional Music. This process is accelerated by the synergy of campuses, stakeholders and related agencies.